2016
DOI: 10.1590/s0100-83582016340300001
|View full text |Cite
|
Sign up to set email alerts
|

Hairy Fleabane as a Source of Major Insect Pests of Soybean

Abstract: -Weeds compete with crops for essential inputs, but they are also important hosts for pests, both during the crop and between crops. Hairy fleabane (Conyza bonariensis) is an important weed growing in both summer and winter crops. The aim of this study was to evaluate the occurrence and population fluctuations of soybean pests using hairy fleabane as an alternative host. Samples of hairy fleabane plants were collected fortnightly over twelve months at two sites (Boa Vista do Incra and São Vicente do Sul) in Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The no-tillage system and herbicide-resistant transgenic plants have favored the increase of herbicide use to control weeds, which has generated great selection pressure on these herbicide-resistant weeds, and as a result has increased the reported cases of resistant weeds (Christoffoleti & Lopez-Ovejero 2008;Carvalho et al 2011;Cerdeira et al 2011;Heap & Duke 2018). This fact is alarming, because it may cause an increase in the seed bank of an area, and consequently the increase of weeds during the off-season, which then serves as a green-bridge for insect pests and diseases (Dalazen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The no-tillage system and herbicide-resistant transgenic plants have favored the increase of herbicide use to control weeds, which has generated great selection pressure on these herbicide-resistant weeds, and as a result has increased the reported cases of resistant weeds (Christoffoleti & Lopez-Ovejero 2008;Carvalho et al 2011;Cerdeira et al 2011;Heap & Duke 2018). This fact is alarming, because it may cause an increase in the seed bank of an area, and consequently the increase of weeds during the off-season, which then serves as a green-bridge for insect pests and diseases (Dalazen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research on insect pests in Conyza sp. plants demonstrated peak A. gemmatalis, S. frugiperda and Helicoverpa gelotopoeon occurrence during the V0-V2 stages of soybean, indicating the role of the weed as a food source for early generations of lepidopteran species (Dalazen et al, 2016). Following crop maturity and harvesting, the authors observed another peak in the presence of the pests on Conyza sp.…”
Section: Resultsmentioning
confidence: 96%
“…Following crop maturity and harvesting, the authors observed another peak in the presence of the pests on Conyza sp. plants, indicating that the caterpillars migrated from soybean plants to the weeds after senescence (Dalazen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations